1980
DOI: 10.1111/j.1600-0714.1980.tb00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic study of periapical lesions 1. Periapical granulomas: clinical, histopathologic and immunohistopathologic studies

Abstract: Seventy periapieal granulomas were histopathologieally examined. They were divided into four types: exudative, granulomatous, granulo-fibrous, and fibrous types, Clinieopathologieally, those having marked lymphoeytie infiltration were found more frequently in eases having had endodontie treatment; further, the size of a radiolueent area did not exeeed that of the involved tooth erown. In eontrast, a predominant plasma eell infiltrate was more frequent in cases with open pulp ehambers (no treatment). In those e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
4

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 32 publications
1
46
0
4
Order By: Relevance
“…Santos et al (12), believe that the inflammatory intensity is not only related to an increased amount of antigen in the lesion, but also to an exacerbated response of the defence mechanisms of the individual. Inflammatory stimulation is thought to cause epithelial proliferation (20), Suzuki et al (3), observed a significant direct correlation between the density of CD1a-labeled cells and the proliferative potential of the epithelium. In this study nuclei positively stained for Ki67 antigen were seen in all epithelialized lesions, in which a higher density of LCs was also observed.…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al (12), believe that the inflammatory intensity is not only related to an increased amount of antigen in the lesion, but also to an exacerbated response of the defence mechanisms of the individual. Inflammatory stimulation is thought to cause epithelial proliferation (20), Suzuki et al (3), observed a significant direct correlation between the density of CD1a-labeled cells and the proliferative potential of the epithelium. In this study nuclei positively stained for Ki67 antigen were seen in all epithelialized lesions, in which a higher density of LCs was also observed.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrostatic pressure of the luminal fluid is important in cyst enlargement and mast cell activity might contribute to this by increasing the osmotic pressure of the fluid in at least three ways: -1) By direct release of heparin into the luminal fluid [3]. 2) By release of hydrolytic enzymes [5][6][7] which could degrade capsular extracellular matrix components thereby facilitating their passage into the fluid.…”
Section: Discussionmentioning
confidence: 99%
“…On degranulation of the mast cell, dissociation of heparin proteoglycan may provide a mechanism for activation of the granule associated proteases [4]. A variety of hydrolytic enzymes are released on degranulation of mast cells [5][6][7] and these enzymes would be expected to degrade components of the connective tissue capsule of odontogenic cysts. Because of poor lymphatic drainage in the cyst wall, these released components would then largely diffuse into the luminal fluid where they would be expected to contribute to increase the osmotic pressure.…”
Section: Introductionmentioning
confidence: 99%
“…11,12) 방사선 사진 상 치근단낭종과 육아종을 감별하는 방법으 로 McCall과 Wald 13) 는 지름이 9.5 mm이상이면 치근단낭 종일 확률이 더 높다는 연구결과에서 치근단낭종은 그 크기 에 근거하여 방사선학적으로 육아종과 감별이 가능하다고 보고하였고, Lalode 14) 는 200 mm 2 …”
unclassified